Sosialisasi Pemanfaatan Dan Pengolahan Sampah Menjadi Biokomposter Dan Kompos Di MA Al Ihsan - Hazan Rudiyanto; Hanifah Efi Rahayu; Hana Larasati; Harnolo Sutaji; Nur Asih Triatmaja (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Socialization activities on the utilization and processing of organic waste in educational institutions play a very important role in fostering awareness, understanding, and responsibility among students towards environmental cleanliness and sustainability. This activity aims to provide basic knowledge and efficient skills in processing organic waste into compost and making simple biocomposters from inorganic waste. This is intended so that students do not look down on waste, whether organic or inorganic. The methods applied in this activity included material delivery, video visualization of the manufacture of simple biocomposters and the production of compost from organic waste, as well as a question and answer session on the material presented, which aimed to measure the students' level of understanding of the material presented. This activity successfully increased the students' understanding of what organic waste is, the types of organic waste, how to make compost from organic waste, how to make a simple biocomposter using inorganic waste as the main material, and the benefits of compost. Therefore, this socialization activity is an effective first step in encouraging students to maintain cleanliness and  preserve the environment.